Study on Learning Motivation of Master’s Students in Management and Leadership at the University of Debrecen - Hajdu, Franciska; Barizsné Hadházi, Edit; Kotsis, Ágnes (International Journal of Engineering and Management Sciences, 2023)
The aim of our study is to present the topic of adult learning. To do this, we first define the definitions and importance of learning in a person’s life. We then turn to the historical background and evolution of adult learning. The motivation of adult learning as a function of different motivational theories is presented. In the second half of the study, an initial research focusing on the motivation of adult learning is presented. The subjects of our research are young adults who are pursuing their master’s degree in management and organization at the Faculty of Economics of the University of Debrecen. We want answers to the extent to which different factors motivate young adults in studying. With the results, we want to give an idea of ​​how the learning motivation of the students can be characterized by both lecturers and human resource professionals working in the private sector. We intend to expand the research to a larger sample in the future.